The Significance of kalapanacatuska w.s.r. to Therapeutic Purification Procedures - Jain, Ankit; Ram, Manohar (International Research Journal of Ayurveda & Yoga, 2020)
The term ‘Samhita’ denotes to whole completion of specific, advantageous knowledge needed for the development of various aspects of life. The term ‘Catuska’ denotes to the set of four chapters having a completion of knowledge relates to a specific subject and possessing the ‘Adhikara’ all over The‘Tantra’. KalpanaCatuska deals with the application of medicine in the form of numerous therapeutic purification procedures in healthy or in ill persons. In the preceding quadrate, information have been furnished about physician, medicine etc. now the various therapeutic measures helping in alleviation of the vitiated dosas, are going to be explained of various therapies which infect constitute them. Thus, oleation, fomentation, emesis and purgation therapy based on the drug having unctuous and other properties are having are be explained here. It comprehended that systemic Samsodhana( therapeutic purification) of entire body is a main pre-requisite for all kinds of preventive and curative procedures. Besides being of preparatory significant; Samsodhanakarma forms a full therapy is aimed to eradicate the vitiated Doshas and to retain a state of normalcy and equilibrium which is fundamental basis of health.